Per una natura linguistica della mente umana: la cognizione sociale alla prova delle specie-specificità verbale - Falzone, Alessandra; Cardella, Valentina (Rivista Italiana di Filosofia del Linguaggio, 2015)
In recent years there has been an increasing amount of research on social cognition. Though the involved disciplines are very different, it seems that they have a common goal: to understand if social cognition is what characterizes us as a species, what makes us extremely different from other animal species. We can say then that the background question of recent studies in cognitive sciences sounds like this: is human cognition marked out by our social skills? According to the most popular perspective in current cognitive sciences, the key of our uniqueness would stay in our peculiar form of shared intentionality, in other words, in our natural inclination to cooperate. It would be a distinctive kind of sociality that makes our species so different from the others. This thesis is grounded on two premises: nothing, in the animal world, compares to our ability to cooperate, and this difference lies just in our peculiar form of social cognition. But both of these premises can be subjected to criticism. A large amount of research in the ethologic field seems to show sophisticated forms of cooperation, among non-human primates above all. In addition, evolutionary studies prove that the peculiar human form of sociality only appears when children begin to learn language. Thus, the aim of this paper is to show that a different interpretation of our cognition, based on species-specific features, can be possible. What makes our cognition something different is the ability to combine skills also present in other species in a new and flexible way, and we have this combinatorial capacity thanks to language. We think that we can use the current research about human cognition to give a different explanation of the classic relation between language and cognition, and that the unique specificity of human cognition precisely lies on this new way to perceive the link between language and cognition